THE CURSE OF THE CHEESE PYRAMID - Stilton, Geronimo; Wolf, Matt (New York : Scholastic Inc., 2004)
Geronimo travels to Egypt to interview Professor Alrat Spitfur and learns the secret of the Seven Wonders of the Ancient Mouse World
"English translation... by Edizioni Piemme S.p.A."--T.p. verso
Keywords: Mice -- Juvenile fiction; Animals -- Juvenile fiction; Stilton, Geronimo (Fictitious character) -- Juvenile fiction